Variations in water use strategies of Tamarix ramosissima at coppice dunes along a precipitation gradient in desert regions of northwest China - Xu, Yanqin; Zhao, Hui; Zhou, Binqian; Dong, Zhengwu; Li, Guangying; Li, Shengyu (Frontiers in Plant Science, 2024)
The precipitation pattern has changed significantly in arid desert areas, yet it is not clear how water use strategies of Tamarix ramosissima Ledeb. on coppice dunes along a natural precipitation gradient are affected. In this study, the hydrogen and oxygen isotope compositions of xylem water, soil water, precipitation, and groundwater were measured by stable isotope techniques in the Huocheng, Mosuowan, and Tazhong. Additionally, the water use strategies of T. ramosissima at coppice dunes along a natural precipitation gradient were investigated in conjunction with the MixSIAR model. The results indicated that the water sources of T. ramosissima exhibited significant variation from semi-arid to hyper-arid areas. In semi-said area, T. ramosissima mainly absorbed shallow, shallow-middle and middle soil water; however, T. ramosissima shifted its primary water sources to middle and deep soil water in arid area. In hyper-arid area, it mainly utilized deep soil water and groundwater. In contrast, the water source contribution rate of T. ramosissima exhibited relative uniformity across each layer in arid area. Notably, in hyper-arid area, the proportion of groundwater by T. ramosissima was significantly high, reaching 60.2%. This is due to the relatively shallow groundwater supplementing the deep soil water content in the area. In conclusion, the proportion of shallow soil water decreased by 14.7% for T. ramosissima from semi-arid to hyper-arid areas, illustrating the occurrence of a gradual shift in potential water sources utilized by T. ramosissima from shallow to deep soil water and groundwater. Therefore, T. ramosissima on coppice dunes shows flexible water use strategies in relation to precipitation and groundwater, reflecting its strong environmental adaptability. The findings hold significant implications for the conservation of water resources and vegetation restoration in arid areas.